Квантово-фармакологические свойства дигоксина - Чекман, И.С.; Казакова, О.А.; Небесная, Т.Ю.; Горчакова, Н.А.; Гунько, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
Quantum pharmacology provides a physical insight into the sequences of processes that are
the basis of drug action related to the pharmacokinetic and phamacodynamic phases. The
results of computation of such quantumpharmacological parameters of cardiac glycoside digoxin as geometrical structure, atomic charges, high occupied and low unoccupied molecular orbital energies, electrostatic potential, total charge density, etc. are analyzed. The free energy of
solvation of digoxin is of importance to understand its complexation properties in the aqueous
media.